DEVELOPMENT OF THE ECONOMIC POTENTIAL OF THE PEOPLE THROUGH THE BAHRUL MAGHFIROH Islamic Boarding School BUSINESS UNIT IN THE ERA OF THE COVID-19 PANDEMIC - Bambang Septiawan; Yuda Kurniawan; M. Alif Sofiyuddin (Universitas Islam Balitar, 2021)
This study aims to find out about the economic development of the people through the business unit owned by the Bahrul Maghfiroh Islamic Boarding School, Malang City. In addition, researchers also want to know the strategy for implementing business unit management during the COVID-19 pandemic. The literature review used refers to the concepts of modern entrepreneurship integrated with Islamic boarding schools. The method used to analyze the data is using the Cresswell model, because it will be easier to find and group research results related to the themes and sub-themes of business unit development. The results that can be concluded from this study are 2 philosophies (main reasons) for the establishment of a business unit at Pondok Pesantren Bahrul Maghfiroh Malang, namely as an education for students to be independent and as a tool to support the welfare of the pesantren (santri). Second, the choice of the type of business that already exists because of the opportunities and potential of the Bahrul Maghfiroh Islamic boarding school in Malang which can be developed for the Bahrul Maghfiroh Islamic boarding school in Malang. Third, maximizing digital marketing and direct marketing is a strategy to anticipate the weakening of the economy during the pandemic at the Bahrul Maghfrioh Islamic Boarding School, Malang. Finally, the result of the business unit at the Bahrul Maghfiroh Islamic Boarding School is the realization of the vision and mission of the Bahrul Maghfiroh Islamic Boarding School in Malang, which is to become a boarding school that has good facilities at a low cost.